Periodic acid Schiff reaction in childhood lymphoblastic leukaemia. The Medical Research Council Working Party on Childhood Leukaemia. - Lilleyman, J; Britton, J; Anderson, L; Richards, S; Bailey, C; Chessells, J (1994)
AIMS: To assess the prevalence and degree of periodic acid Schiff (PAS) positivity in blast cells from children with lymphoblastic leukaemia (ALL); its association with other disease characteristics; and its clinical importance in predicting the outcome of treatment. METHODS: Marrow slides from entrants to a large United Kingdom multicentre ALL trial (UKALL X) were batch processed and assessed blind for PAS positivity by one morphologist. Patients were classified into groups A, B, and C, corresponding to less than 1% PAS positive cells, 1-10%, and over 10%, respectively. Their PAS pattern was then compared with other clinical and pathological features of ALL and with treatment outcome. RESULTS: Slides from 921 children were examined of which 371 (40%) were categorised as group A, 324 (35%) as group B, and 226 (25%) as group C. There was a clear association between the presence of blast cell vacuoles on Romanowsky staining and PAS positivity. Group A (PAS negative) patients included a disproportionate excess of those with L2 morphology, those under 2 or over 6 years of age, those with an initial white cell count over 50 x 10(9)/l, those with a T or null cell immunophenotype, and those with chromosomal abnormalities other than "high hyperdiploidy". Four years from diagnosis, group C patients had an 8% disease free survival advantage over those in group A (2p = 0.01). This was irrespective of initial white cell count, but not of immunophenotype or the presence of vacuoles. CONCLUSIONS: Strong PAS positivity is a feature of "common" ALL and is particularly associated with blast cell vacuoles. It does occasionally occur in other disease subtypes with or without vacuoles. It predicts a better response to current treatment, but not independently of other cell characteristics.